Magnetic-field Order in the Southwestern Rim of RCW 86 Constrained Using X-Ray Polarimetry - Silvestri, Stefano; Prokhorov, Dmitry; Vink, Jacco; Slane, Patrick; Yang, Yi-Jung; Bucciantini, Niccolo; Ferrazzoli, Riccardo; Zhou, Ping; Costa, Enrico; Omodei, Nicola; Ng, Chi-Yung; Soffitta, Paolo; et al. (Institute of Physics Publishing, 2026)
RCW 86 is a supernova remnant whose origin has recently been linked to an off-center explosion within a cavity created by its progenitor star. In the southwestern region, the forward shock is thought to have reached the cavity wall, encountering diverse environmental conditions. We report on the spatially resolved X-ray polarimetric observation of RCW 86 with the Imaging X-ray Polarimetry Explorer (IXPE). In the 2–4.5 keV energy band we find no significant detection of polarization. Employing a dedicated background subtraction procedure and Bayesian spectropolarimetric fitting, we derive 99% upper limits on the polarization degree of the synchrotron component: 15% in higher-statistics regions and 30%–40% in lower-statistics regions. These upper limits on the polarization degree in several regions exclude the possibility of a strongly coherent magnetic field down to the subparsec scale, and that of a moderately coherent one on the scale of the synchrotron features as resolved by IXPE. The results indicate that the shocks in the southwestern rim of RCW 86 propagate more slowly than the unshocked ejecta at their locations, yet exceed the measured proper motion speeds. This behavior is consistent with reflected shocks occurring in tenuous regions of the shocked ejecta, distinct from regions that are radio-bright.